Photosynthesis - Hall, D. O. (David Oakley); Rao, K. K.; Institute of Biology (New York : Cambridge University Press, 1999)
Illustrations, color plates, and text help describe the process of photosynthesis and its roll in biochemical, biophysical, and genetic studies.
"Published in association with the Institute of Biology.".
Includes bibliographical references (p. [203]-210) and index.
Adult
Keywords: Photosynthesis; Photosynthesis